KONTRIBUSI KEKUATAN OTOT LENGAN DAN BAHU DAN KELENTUKAN OTOT PUNGGUNG DENGAN KEMAMPUAN GULUNGAN PINGGANG DALAM CABANG OLAHRAGA GULAT ATLIT PUTRA PPLP RIAU - Nani Maryani; Saripin Saripin; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on the observations that researchers have done on PPLP RIAU wrestling athletes found some problems, among others, at the time of the striker's roll was overpowered by the opponent who in turn on it.terrelnya embrace of arms in the abdomen, at the time of the motion of the series of scrolls, the back is still attached to the mat and there is a restrained movement resulting in a loss. This study aims to determine how big the contribution of muscle strength of the arms and shoulders and back muscle formation to the ability of the waist roll (abdomen). Population in this research all object of research, that is atlet wrestling put PPLP Riau as many as 10 people. Sampling using total sampling. The data collection techniques used in this study are muscle strength test of arm and shoulder with Expanding dynamometer. Test back muscle elongation with Sit and reach and Test the ability of the waist coil with the waist guard test. Based on the results of research that has been authors described in the previous chapter, it can be concluded as follows that From the results obtained correlation analysis between arm muscle strength and shoulder and waist coil ability, where rtab at significant level α (0.05) = 0.666 means , rhitung (0.678)> rtab (0.666), with a contribution of 45.97%. meaning the hypothesis is accepted and there is a meaningful relationship between the muscle strength of the arms and shoulders with the ability of the waist coil on the athletes of PPLP Riau. From result obtained by correlation analysis between kelototot back and waist coil ability, where rtab at significant level α (0,05) = 0,666 means, rhitung (0,802)> rtab (0,666), with contribution equal to 64,32% meaning hypothesis accepted and there is a significant relationship between the back muscle formation with the ability of the waist coil on the athletes PPLP Riau.Terdapat relationship jointly between the muscle strength of the arms and shoulders and flexibility of the back muscles to the ability of the waist coil on athletes PPLP Riau With a significant level α = 0.05 with the contribution amounted to 62.99%. Keywords: Muscle Strength Engan And Shoulder, Back muscle, Waist Guage